Pembangunan Sistem Informasi Penggajian Karyawan Dengan Menggunakan Model Rapid Application Development - Hidayati, Nur (STIKOM Tunas Bangsa Pematangsiantar, 2021)
Payroll is a form of compensation given to employees as a form of appreciation for their work. For this reason, an organization or company must be able to manage its employee agreements properly and correctly, because it is related to employee welfare. At this time, there are still many organizations that do not have a good payroll information system. This can cause problems such as errors in making a salary recap caused because the data processing is still done manually. Besides that, making a payroll report takes a long time, because the payroll data documentation is still not neatly arranged. With this problem, the existing payroll information system is less effective. Therefore, it is necessary to develop a better payroll information system, with the aim of helping solve these problems. To achieve this goal, it is necessary to have an appropriate model in system development such as the use of the Rapid Application Development (RAD) model. With this RAD model, it will be clearer the stages that must be carried out in system development, so as to produce a payroll program application that can help solve existing problems